Assessing Biodiversity E-Modules: PBL-Google Sites for Digital Literacy & Engagement - Lilia Krisna Sari; Marlina Ummas Genisa; Meli Astiani (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Digital revolution in education necessitates the utilisation of interactive and contextual learning media, particularly in the presentation of biological content, such as biodiversity. Nevertheless, traditional learning predominates, thereby diminishing student engagement in the educational process. This study seeks to evaluate the necessity for the creation of Problem-Based Learning (PBL) e-modules utilising the Google Sites platform to improve students' digital literacy and engagement in learning. The employed methodology is descriptive quantitative, involving the distribution of questionnaires to 80 students and 6 biology instructors at SMAN 1 and SMAN 9 OKU. The research findings indicate that most students exhibit a preference for digital learning resources and favour interactive learning approaches, including conversations and problem-solving activities. Furthermore, both students and educators concur on the necessity of creating digital learning resources that foster 21st-century competencies, including critical and collaborative thinking. The subject of biodiversity was recognised as particularly pertinent for development through the PBL methodology. This discovery underscores the necessity of incorporating digital technology in education to foster a more engaging, significant, and needs-based learning experience for pupils.